Growth regulators in the vegetative development of Agave durangensis Gentry vitroplants - Dévora-Rodríguez, Daniela Guadalupe; Pulido-Díaz, Cecilia; Chávez-Simental, Jorge Armando; Ortiz-Sánchez, Ixchel Abby; Loera-Gallegos, Héctor Manuel; Prieto-Ruiz, José Ángel (Ecosistemas y Recursos Agropecuarios, 2021)
The effect of cytokinins and auxins on the production ofadventitious shoots of Agave durangensis in vitro was studied. Germinationwas done in Murashige and Skoog (MS) culture medium at 50%concentration without growth regulators was used. The production anddevelopment of adventitious shoots was carried out in a 100% MS culturemedium with cytokinins (KIN and BAP) and ANA as auxin, evaluatingdifferent concentrations in 12 treatments. The concentration of 4.0 mg L-1of BAP without auxins presented better results in explant height, number ofleaves per explant, number of shoots per explant and number of leaves pershoot. The presence of auxins only favored the height of the sprout in thetreatment of 4.0 mg L-1 KIN and 0.4 mg L-1 ANA. Therefore, it is feasible touse only cytokinins on culture medium in the shoots production stage of A.durangensis.